2019
DOI: 10.1016/j.ygeno.2018.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Integration of miRNA weighted gene co-expression network and miRNA-mRNA co-expression analyses reveals potential regulatory functions of miRNAs in calf rumen development

Abstract: This study aimed to explore the roles of microRNAs (miRNAs) in calf rumen development during early life. Rumen tissues were collected from 16 calves (8 at pre-weaning and 8 at post-weaning) for miRNA-sequencing, differential expression (DE), miRNA weighted gene co-expression network (WGCNA) and miRNA-mRNA co-expression analyses. 295 miRNAs were identified. Bta-miR-143, miR-26a, miR-145 and miR-27b were the most abundantly expressed. 122 miRNAs were significantly DE between the pre- and post-weaning periods and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 58 publications
3
33
0
Order By: Relevance
“…Accompanied by the development of rumen size, rumen papillae and muscular tissues, gene expression were also remarkably altered though transcriptional and post-transcriptional regulation. Plenty of differential expressed genes (DEGs) have been identi ed in cattle between pre-and post-weaning [2,35,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accompanied by the development of rumen size, rumen papillae and muscular tissues, gene expression were also remarkably altered though transcriptional and post-transcriptional regulation. Plenty of differential expressed genes (DEGs) have been identi ed in cattle between pre-and post-weaning [2,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, 122 DEMs were identi ed from 260 known and 35 novel miRNAs in the same rumen tissues. Among them, six miRNAs (miR-143, miR-29b, miR-145, miR-493, miR-26a and miR-199) were identi ed as the key regulators of rumen development in cattle [36]. However, the studies about miRNAs in goat rumens still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental details have been described in our previous studies [ 23 , 24 ]. Briefly, sixteen 2–7 days-old Holstein calves were raised for a period of 96 days in individual pens.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we characterized the long non-coding RNA (lncRNA) expression in ileum tissues of calves and functional inference of identified lncRNA (623 known and 1505 novel) cis target genes revealed potential roles in growth and development as well as in posttranscriptional gene silencing by RNA or miRNA processing processes and in disease resistance mechanisms [ 23 ]. Moreover, we also observed that 122 miRNAs were significantly differentially expressed between the pre- and post-weaning periods in the rumen, suggesting important roles of miRNAs in calf gut during early life [ 24 ]. Therefore, we hypothesize that miRNAs might play important roles in ileum development during the pre- and post-weaning periods.…”
Section: Introductionmentioning
confidence: 99%
“…Still, large information about DPC roles in growth and e resistance to stress regulation is unknown. Herein, we used Weighted Gene Co-expression Network Analysis (WGCNA), a mathematical method to identify key gene network and hub genes [38][39][40]. The present study was conducted which focused on the transcriptome changes by DPC treatment using Illumina Hiseq 4000 platform.…”
Section: Introductionmentioning
confidence: 99%